Characterizing the changes to the material properties of a bottle‐grade poly(ethylene terephthalate) subject to repeated melt extrusion. Issue 13 (30th January 2023) - Hatt, Jonathan; Englund, Karl; Li, Hui
Abstract: According to 2018 data from the National Association of PET Container Resources, it is estimated that the recycling rate of the poly(ethylene terephthalate) (PET) bottle in the US is 29%. Trailing this figure is the amount of recycled PET bottles that are utilized for future applications, which is estimated at 20%. Over the previous decade, both values have remained relatively unchanged due to the dynamics of various factors. Ironically, one contributing factor is the mechanical recycling process itself, particularly if the material has been previously exposed. Repeated exposure to mechanical recycling can degrade the properties of the PET, limiting future utilization and in severe cases, destining the material for the landfill. Given the importance of the material properties to the proper functioning of the PET in a bottle application, it is imperative to understand how the properties of the material change when subject to repeated mechanical recycling. The aim for this research was to investigate how the properties of a virgin, bottle grade PET change when subject to a repeated step of the mechanical recycling process, melt extrusion. After each successive extrusion, changes in the thermal, rheological and mechanical properties were measured and compared to the virgin values. Abstract : Subjecting a bottle‐grade poly(ethylene terephthalate) to repeated melt extrusion yields measurable changes in the molecular weight and corresponding rheological, thermal and mechanical properties of the polymer. These changes result from thermal‐mechanical degradative processes that are inflicted upon the material during the melt extrusion process.